2013
DOI: 10.25011/cim.v36i2.19572
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of dexmedetomidine on bupivacaine-induced sciatic nerve inflammation is mediated by mast cells

Abstract: Purpose: This study was designed to assess the correlation between the neuroprotective effect of dexmedetomidine and oxidative stress, neural inflammation and mast cell stability in rats with bupivacaine-induced sciatic nerve toxicity. Methods: Forty adult Wistar Albino rats, eight rats per group, were used. Saline (0.3 ml of 0.9%), dexmedetomidine (20 µg/kg), 0.5% bupivacaine or 0.5% bupivacaine+dexmedetomidine (20 µg/kg) was injected into the sciatic nerve. A control group of rats received no injection. Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 37 publications
(41 reference statements)
1
40
0
Order By: Relevance
“…The likely mechanism was stabilisation of mast cells at the injury site. 15 These data build on previous research of clonidine's a 2A -mediated neuroprotective effects in rat nerve injury models. 16 This has led to dexmedetomidine being characterised by some as the most promising of the adjuvants currently available.…”
supporting
confidence: 53%
“…The likely mechanism was stabilisation of mast cells at the injury site. 15 These data build on previous research of clonidine's a 2A -mediated neuroprotective effects in rat nerve injury models. 16 This has led to dexmedetomidine being characterised by some as the most promising of the adjuvants currently available.…”
supporting
confidence: 53%
“…However, in animal models of spinal anesthesia and sciatic nerve block, dexmedetomidine did not show toxicity and was potentially neuroprotective when combined with lignocaine and bupivacaine. [2021] The published data support the efficacy of dexmedetomidine for peripheral nerve block prolongation of approximately 200 min at doses around 1 mcg/kg, and it appears to be a viable option as an additive to local anesthetics, especially where bradycardia and hypotension is an issue.…”
Section: Discussionmentioning
confidence: 94%
“…Recent studies found that dexmedetomidine has an anti-inflammatory effect by reducing the serum levels of inflammatory cytokines, however, the upstream mechanism is still unknown [46]. In the present study, we used a surgical procedure and perineural injection to induce a background inflammatory response (e.g., increasing IL-6 and TNF-α levels) in sciatic nerve tissue to investigate the anti-inflammatory effect of perineural administration of dexmedetomidine and the underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies found that dexmedetomidine has an anti-inflammatory effect through reducing the serum levels of inflammatory factors, which may extend its application in the clinic [46]. However, the upstream mechanism by which dexmedetomidine reduces inflammatory factors levels remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%